2018
DOI: 10.1097/gox.0000000000001846
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravenous Meloxicam in Subjects with Moderate-to-severe Pain Following Abdominoplasty

Abstract: Background:A nanocrystal intravenous (IV) formulation of meloxicam is being studied with the aim of providing postoperative analgesia.Methods:This randomized, multicenter, double-blind, placebo-controlled trial evaluated meloxicam IV 30 mg or placebo (≤ 3 doses) in 219 subjects undergoing abdominoplasty. The primary endpoint was the summed pain intensity difference over 24 hours postdose (SPID24).Results:Meloxicam IV–treated subjects had a statistically significant reduction in the least squares mean of SPID24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…32 In the abdominoplasty study, subjects who received meloxicam IV had a statistically significant reduction in PI as measured by the summed PI difference from hour 0 to hour 24 compared with placebo-treated subjects (-4262.1 versus -3535.7; P = .0145). 31 Subjects randomized to meloxicam IV 30 mg in the bunionectomy study experienced a statistically significant difference in summed PI difference from hour 0 to hour 48 versus the placebo group (-6956.0 versus -4829.3; P = .0034). 32 In both phase 3 studies, meloxicam IV was generally well tolerated, with a safety profile that included a low incidence of adverse events that was comparable to that of placebo.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…32 In the abdominoplasty study, subjects who received meloxicam IV had a statistically significant reduction in PI as measured by the summed PI difference from hour 0 to hour 24 compared with placebo-treated subjects (-4262.1 versus -3535.7; P = .0145). 31 Subjects randomized to meloxicam IV 30 mg in the bunionectomy study experienced a statistically significant difference in summed PI difference from hour 0 to hour 48 versus the placebo group (-6956.0 versus -4829.3; P = .0034). 32 In both phase 3 studies, meloxicam IV was generally well tolerated, with a safety profile that included a low incidence of adverse events that was comparable to that of placebo.…”
mentioning
confidence: 93%
“…In phase 2 trials of subjects with postoperative pain after surgical procedures including removal of impacted third molars, open abdominal hysterectomy, laparoscopic abdominal surgery, and bunionectomy, meloxicam IV exhibited onset of analgesia within 15 minutes or less postdose, with maintenance of the analgesic effect through the 24‐hour dosing period. The analgesic effect and safety of meloxicam IV were evaluated in 2 phase 3 surgical models, including soft‐tissue surgery (abdominoplasty) and hard‐tissue surgery (bunionectomy) . In the abdominoplasty study, subjects who received meloxicam IV had a statistically significant reduction in PI as measured by the summed PI difference from hour 0 to hour 24 compared with placebo‐treated subjects (‒4262.1 versus ‒3535.7; P = .0145) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It belongs to the oxicam family of chemicals and blocks COX-2 more than it does COX-1, thus having fewer gastrointestinal side effects compared to nonselective NSAIDs, and without interfering with platelet function [29,30]. Its e cacy and safety have been evaluated in seven Phase 2/3 randomized controlled clinical trials (RCTs) following procedures including dental surgery, abdominal hysterectomy, bunionectomy, abdominoplasty, and other major procedures [31][32][33][34][35][36][37]. Since these trials did not allow concomitant NSAID use and were placebo controlled, MIV has not yet been compared to other non-opioid IV analgesics.…”
Section: Introductionmentioning
confidence: 99%
“…A nanocrystal formulation of meloxicam that can be administered by intravenous bolus injection was developed for the management of moderate to severe pain. Intravenous meloxicam was evaluated in four phase II and three phase III postoperative studies, comprising subjects undergoing dental impaction surgery,3 open abdominal hysterectomy,4 abdominal laparoscopic surgery,5 bunionectomy,6 7 abdominoplasty8 and major surgery 9. In these studies, intravenous meloxicam demonstrated onset of analgesia within 15 min after administration with maintenance over a 24-hour dosing interval 3 4 6–8.…”
Section: Introductionmentioning
confidence: 99%